Dopant concentration dependence of thermostimulated luminescence in Li₂B₄O₇:Mn single crystals - Holovey, V.M.; Lyamayev, V.I.; Birov, M.M.; Puga, P.P.; Solomon, A.M. (Functional Materials, 2005)
А series of Li₂B₄О₇:Mn single crystals with different dopant concentrations has been produced and their thermoluminescence (TL) has been studied. The glow curve shapes differ significantly with increase of Mn concentration, but all of them reveal two broad complex peaks. The results of fractional glow technique application show the presence of two groups, each with a large number of traps with close depths. Dose dependence of glow curves shape testifies to the first order of TL kinetics.